Feminization of migration and trends in remittances - Maelan Le Goff (IZA World of Labor, 2016)
Migrants' remittances to developing countries have increased in recent decades, partly due to reduced transactions costs and improved living conditions in host countries. The feminization of international migration represents yet another explanation. Despite the difficulties female migrants encounter in the labor market, their total remittances may be higher and more resilient than those of male migrants, owing to these women's stronger links to family members left behind and self-insurance motives. Policymakers need to understand how this new and significant upward trend in female migration could affect the economic and social development of home countries.
Keywords: F22; F24; J16; 330; remittances; female migrants; developing countries